2017
DOI: 10.31234/osf.io/f7tpn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individual differences in decoding skill, print exposure, and cortical structure in young adults

Abstract: This exploratory study investigated relations between individual differences in cortical grey matter structure and young adult readers' cognitive profiles. Whole-brain analyses revealed neuroanatomical correlations with word and nonword reading ability (decoding), and experience with printed matter. Decoding was positively correlated with grey matter volume (GMV) in left superior temporal sulcus, and thickness (GMT) in right superior temporal gyrus. Print exposure was negatively correlated with GMT in left inf… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 111 publications
0
1
0
Order By: Relevance
“…In fact, print exposure represents the accumulated reading experience a person has acquired throughout his/her lifetime, a dimension that is directly linked to our prior knowledge, and therefore, to our crystalized intelligence (Horn & Cattell, 1966). Recent neuroscientific evidence has shown that print exposure is correlated with grey matter cortical thickness in the left inferior frontal gyrus and the left fusiform gyrus, suggesting reading experience might be connected to maturational brain processes that are related to skill consolidation (Goldman & Manis, 2013; Johns et al, 2018). In addition, print exposure has been associated with many verbal abilities such as vocabulary size, syntactic and phonological processing, verbal fluency, and other higher-level text comprehension processes (e.g., Acheson, Wells & MacDonald, 2008), usually related to crystalised rather than fluid intelligence (Cattell, 1971; Stamenković & Holyoak, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, print exposure represents the accumulated reading experience a person has acquired throughout his/her lifetime, a dimension that is directly linked to our prior knowledge, and therefore, to our crystalized intelligence (Horn & Cattell, 1966). Recent neuroscientific evidence has shown that print exposure is correlated with grey matter cortical thickness in the left inferior frontal gyrus and the left fusiform gyrus, suggesting reading experience might be connected to maturational brain processes that are related to skill consolidation (Goldman & Manis, 2013; Johns et al, 2018). In addition, print exposure has been associated with many verbal abilities such as vocabulary size, syntactic and phonological processing, verbal fluency, and other higher-level text comprehension processes (e.g., Acheson, Wells & MacDonald, 2008), usually related to crystalised rather than fluid intelligence (Cattell, 1971; Stamenković & Holyoak, 2018).…”
Section: Discussionmentioning
confidence: 99%